Bilateral Simultaneous Nonarteritic Anterior Ischemic Optic Neuropathy after Ingestion of Sildenafil for Erectile Dysfunction - Anna Tarantini; Alessandra Faraoni; Francesca Menchini; Paolo Lanzetta (Case Reports in Medicine)
Purpose. To describe a patient who developed bilateral, simultaneous nonarteritic anterior ischemic optic neuropathy (NAION) after ingestion of Sildenafil citrate (Viagra) for erectile dysfunction. Methods. Observational case report. Results. A 60-year-old diabetic man noted sudden decrease of vision in both eyes 16 hours after his third consecutive 50 mg daily Sildenafil ingestion. A diagnosis of bilateral NAION was made and he was treated for three days with methylprednisolone 1 g/d intravenously, followed by oral prednisone 75 mg/d. Final visual acuity was 20/50 right eye (OD) and 20/20 left eye (OS). He had preexisting diabetes. Conclusion. This is the first reported case of simultaneous bilateral NAION occurred in a diabetic patient early after Sildenafil intake. Patients with predisposing conditions such as diabetes have to be warned against the use of PDE inhibitors.